Solitary Dermal Melanoma: Beginning or End of the Metastatic Process? - Lee, Chris C. (2009)
BACKGROUND: Solitary dermal melanoma (SDM) is confined to the dermal and/or subcutaneous tissue without an epidermal component. It is unclear whether this lesion is a subtype of primary melanoma or distant cutaneous metastasis from an unknown primary. We evaluated our large experience to determine the prognosis and optimal management of SDM. METHODS: Our melanoma referral center's database of prospectively acquired records was used for identification and clinicopathologic analysis of patients presenting with SDM between 1971 and 2005. RESULTS: Of 12,817 database patients during a 34-year period, 101 (0.8%) presented with SDM. Of 92 patients free of distant metastasis on initial presentation, 55 (60%) were observed and 37 (40%) underwent nodal staging by elective or sentinel lymphadenectomy: regional metastases were identified in 7 (19%). Nodal recurrence occurred in 1 (3.3%) of 30 patients with histopathology-negative nodes, as compared with 13 (24%) of 55 patients who underwent nodal observation instead of nodal staging. Thus, 21 (23%) of 92 patients had nodal metastasis identified during surgical nodal staging or postoperative nodal observation. At a median follow-up of 68 months, estimated 5-year overall survival rate was 73% for 71 patients with localized disease versus 67% for 21 patients with regional disease (P=0.25) versus 22% for 9 patients with distant disease (P=0.009, regional versus distant disease). CONCLUSIONS: SDM resembles intermediate-thickness primary cutaneous melanoma with respect to prognostic characteristics and clinical evolution, but its rate of distant metastasis justifies radiographic staging and its high rate of regional node metastasis justifies wide excision and sentinel lymphadenectomy.